Self-Harming Behavior Among Students in the Medical Program at Yarsi University and Its Review From an Islamic Perspective - Fudia Zalza Nabilla; Citra Fitri Agustina; Karimulloh Karimulloh; Miranti Pusparini (Green Publisher Indonesia, 2026)
Self-harm is a self-injurious behavior that commonly occurs among young adults, including medical students who are highly susceptible to academic and psychological stress. This study aims to describe the tendency of self-harm among medical students at YARSI University and review it from an Islamic perspective. A quantitative descriptive design was applied using the Self-Harm Inventory (SHI) as the research instrument. The study involved 141 participants selected through total sampling, and the data were analyzed descriptively. The findings revealed that all respondents (100%) exhibited a tendency toward self-harm, with an average score of 30.11 (range 22–71). Most respondents were categorized as low (49.6%), followed by moderate (34.8%) and high (15.6%). The majority experienced low levels of psychological and academic impact. Predominantly, respondents were female, 20 years old, and from the 2022 cohort. From an Islamic perspective, self-harm is strictly prohibited as it represents self-destruction, aligning with the prohibition stated in Surah An-Nisa :29. These findings underscore the need for comprehensive interventions that combine psychological support, academic guidance, and spiritual reinforcement to prevent self-harm among medical students.